Observations of the incipient and penultimate stages of Holocene marine terrace development. Issue 13 (24th July 2022) - Dickson, Mark E.; Omidiji, Jokotola; Litchfield, Nicola J.; Norton, Kevin P.; Matsumoto, Hironori; Krier‐Mariani, Raphael L.; Horton, Sophie L.; Acharya‐Chowdhury, Lovleen; McLean, Aidan D.; Hurst, Martin D.; Stephenson, Wayne J.
Abstract: Flights of Holocene marine terraces are useful for reconstructing past earthquakes, but coastal erosion can remove terraces from the landscape, potentially leading to incorrect estimates of earthquake magnitude and frequency. Relatively little effort has been afforded to studying terrace erosion processes, and this paper presents the first field evidence that we are aware of documenting terrace erosion rates. Two case studies from New Zealand provide a unique opportunity to observe the beginning and end phases of terrace development. We present downwear and backwear erosion measurements, showing that both sets of processes are important. Micro‐erosion meter measurements from Kaikōura Peninsula, South Island, confirm that downwear processes are modifying new marine terraces that were created when the peninsula was uplifted about 1 m during the 2016 earthquake. Erosion rates were high immediately following uplift as the relatively barren intertidal rock shore platform rapidly transformed into an incipient marine terrace with cover deposits. However, the Kaikōura earthquake uplifted shore platforms only a small distance above the upper tidal limit and ongoing downwear and backwear erosion may begin to remove parts of this terrace in future decades. We explored this prospect with a case study at Māhia Peninsula, North Island, where 100–300 years have elapsed since the last terrace‐forming earthquake. Historical photographs were used to document about 80 years of backwear erosion. Terrace erosion rates have been nearly constant through this period, and extrapolation implies that the terrace will be removed in places by 2030. The erosion data in this paper provide new insights into how terraces can be removed from the landscape, but there are many complicating factors. To help understand these factors we present a new conceptual model of marine terrace creation and destruction for soft‐rock coasts. Abstract : Coastal erosion can remove marine terraces from the landscape, complicating interpretation of past earthquakes. We measured terrace erosion rates at two field sites where we had a unique opportunity to study the beginning and end phases of terrace development. Photograph (a) at Kaikōura shows a new marine terrace produced by the 2016 earthquake. Photograph (b) at Mahia shows a narrow terrace that has nearly been removed by erosion.